On the Invalidity of Pontella marplatensis Ramírez, 1966, a Synonym of P. patagoniensis (Lubbock, 1853) (Copepoda, Pontellidae) - Derisio, Carla María (2011)
We recently examined new specimens collected from coastal waters off Mar del Plata (Buenos Aires Province, Argentina) and the comparison with Lubbock’s text and drawings showed unequivocal evidence that they correspond to Pontella patagoniensis.